Electrolyte additive, electrolyte, battery and electric device

By using electrolyte additives containing the compound of Formula 1 and the chain compound protector in lithium-ion batteries, the problems of gas production, bulging and capacity attenuation of lithium-ion batteries under high temperature conditions are solved, and higher high-temperature storage and cycling performance are achieved.

CN119852515APending Publication Date: 2025-04-18GUANGZHOU TINCI MATERIALS TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311341961.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems such as gas production, bulging and capacity attenuation under high temperature conditions, mainly due to the poor thermal stability of the SEI film formed by carbonate solvents.

Method used

An electrolyte additive including the compound represented by Formula 1 and a protective agent is a chain compound with an unsaturation of more than or equal to 3, which can react with the free radical containing sulfonate groups to reduce the decomposition of the cyclic solvent and the damage of the SEI film.

Benefits of technology

By reducing the catalytic decomposition of the cyclic solvent by free radicals, the gas generated by the decomposition of the cyclic solvent at high temperatures is suppressed, the volume expansion of the battery is reduced, the high-temperature storage performance is enhanced, the conductivity and strength of the SEI film are improved, and the high-temperature cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852515A_ABST
    Figure CN119852515A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte additive, an electrolyte, a battery and a power utilization device, the electrolyte additive comprises a compound shown in the formula 1 and a protective agent, the protective agent # imgabs0 comprises a chain compound with the unsaturation degree larger than or equal to 3, the protective agent can be subjected to addition reaction with a sulfonate group-containing free radical formed after the ring-opening reaction of the compound as shown in the formula 1. Therefore, when the electrolyte additive is added into the lithium ion battery, the high-temperature cycle performance and the high-temperature storage performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of batteries, and specifically relates to an electrolyte additive, an electrolyte, a battery and an electrical device. Background Art

[0002] At present, commercial electrolytes are usually obtained by dissolving lithium salts in linear / cyclic carbonate solvents. For example, ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), etc. are all commonly used carbonate solvents. They can not only determine the physical properties of the electrolyte, but also form a SEI film (solid electrolyte interface) at the negative electrode-electrolyte interface to ensure the cycle stability of the battery. However, the SEI film formed based on the decomposition of the solvent has poor thermal stability, which leads to the aggravation of the side reactions of the electrolyte under high temperature conditions, resulting in gas production, etc. Therefore, lithium-ion batteries usually have negative effects such as bulging and rapid capacity decay under high temperature conditions. In view of the limited protection ability of the SEI film formed by carbonate solvents at the negative electrode-electrolyte interface, cyclic sulfonate additives have attracted widespread attention in the field of electronic products and power batteries because they can form a stable SEI film (the SEI film is rich in alkyl sulfonate lithium and inorganic sulfide) and can inhibit the gas production of the battery under high temperature conditions.

[0003] In terms of improving the performance of lithium batteries, 1,3-propane sultone (PS) is a representative sulfonate additive, which has good performance in improving the high-temperature cycle performance and high-temperature storage performance of batteries. However, due to the control of EU REACH regulations, the amount of PS added cannot exceed 0.8% of the total mass of the electrolyte. The amount of PS added to the electrolyte often needs to be ≥1% to meet the needs of use, so it is necessary to provide an electrolyte additive that can simultaneously improve the high-temperature cycle performance and high-temperature storage of the battery. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide an electrolyte additive, an electrolyte, a battery and an electrical device, which can improve the high temperature cycle performance and high temperature storage performance of the battery by adding the electrolyte additive to the lithium ion battery.

[0005] In a first aspect, the present application provides an electrolyte additive, comprising a compound shown in Formula 1 and a protective agent.

[0006]

[0007] The protective agent comprises a chain compound with an unsaturation degree greater than or equal to 3, and the protective agent can undergo an addition reaction with a free radical containing a sulfonate group formed after the ring-opening reaction of the compound represented by Formula 1.

[0008] The electrolyte additive of the present application includes a compound shown in Formula 1 and a protective agent. The electrolyte additive is added to a lithium ion battery. During the formation and circulation process, the compound shown in Formula 1 can undergo a ring-opening reaction to produce a free radical containing a sulfonate group. The protective agent of the present application includes a chain compound with a degree of unsaturation greater than or equal to 3, which has a high activity and can preferentially react with the free radical containing a sulfonate group generated by the compound shown in Formula 1 before the cyclic solvent in the electrolyte, that is, the catalytic decomposition of the sulfonate group by the free radical containing the sulfonate group on the cyclic solvent is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high-temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to produce a free radical containing a sulfonate group, which reacts with the protective agent to form a dense SEI film rich in S elements on the negative electrode surface, which can improve the conductivity of the SEI film and improve the power performance of the battery. The SEI film has a high strength, which reduces the damage and recombination of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery. Therefore, adding the electrolyte additive to lithium-ion batteries can improve the battery's power performance, high-temperature cycle performance, and high-temperature storage performance.

[0009] In some embodiments, the protective agent includes a chain compound with an unsaturation degree of 3 to 8. Thus, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0010] In some embodiments, the mass ratio of the compound represented by Formula 1 to the protective agent is 0.7-11: 1. Thus, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0011] In some embodiments, the chain compound having an unsaturation degree greater than or equal to 3 includes at least one of a silane compound, a carbonate compound, and a sulfonate compound. Thus, the power performance, high temperature cycle performance, and high temperature storage performance of the battery can be improved.

[0012] In some embodiments, the silane compound includes a compound represented by Formula 2: Wherein, R1, R2, R3, and R4 are independently hydrogen, fluorine, an alkyl group having 1 to 10 carbon atoms, a silane group having 1 to 10 carbon atoms, a siloxane group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an alkenylsiloxane group having 2 to 10 carbon atoms, or an alkynylsiloxane group having 2 to 10 carbon atoms. Thus, the power performance, high temperature cycle performance, and high temperature storage performance of the battery can be improved.

[0013] In some embodiments, R1, R2, R3, and R4 in Formula 2 are independently methyl, vinyl, ethynyl, ethynyldimethylsiloxane, or trivinylsiloxane. Thus, the power performance, high temperature cycle performance, and high temperature storage performance of the battery can be improved.

[0014] In some embodiments, the silane compound includes at least one of the following compounds:

[0015]

[0016] Thereby, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0017] In some embodiments, the carbonate compound includes a compound represented by Formula 3: Among them, A is an alkenyl group with 2 to 6 carbon atoms or an alkynyl group with 2 to 6 carbon atoms, R5 and R6 are independently hydrogen, fluorine, an alkyl group with 1 to 10 carbon atoms, an alkenyl group with 2 to 10 carbon atoms, an alkynyl group with 2 to 10 carbon atoms, an alkyl carbonate group with 2 to 10 carbon atoms, an alkyl sulfonate group with 1 to 10 carbon atoms, or a fluoroalkyl group with 1 to 10 carbon atoms, and at least one of R5 and R6 is an alkyl carbonate group with 2 to 10 carbon atoms. Thus, the power performance, high temperature cycle performance, and high temperature storage performance of the battery can be improved.

[0018] In some embodiments, R5 and R6 in Formula 3 are alkyl carbonate groups having 1 to 10 carbon atoms, preferably diethyl carbonate groups. Thus, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0019] In some embodiments, the carbonate compound includes at least one of the following compounds:

[0020]

[0021] Thereby, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0022] In some embodiments, the sulfonate compound includes a compound represented by Formula 4:

[0023] Wherein, R7 and R8 are independently hydrogen atom, fluorine atom, alkyl group with 1 to 10 carbon atoms, fluoroalkyl group with 1 to 10 carbon atoms, alkenyl group with 2 to 10 carbon atoms, and alkynyl group with 2 to 10 carbon atoms. Thus, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0024] In some embodiments, R7 and R8 in Formula 4 are independently methyl, trifluoromethyl, ethynyl, vinyl or fluorine atoms, thereby improving the power performance, high temperature cycle performance and high temperature storage performance of the battery.

[0025] In some embodiments, the sulfonate compound includes at least one of the following compounds:

[0026] Thereby, the power performance, high temperature cycle performance and high temperature storage performance of the battery can be improved.

[0027] The second aspect of the present application provides an electrolyte, comprising the electrolyte additive described in the first aspect. Thus, adding the electrolyte to a lithium-ion battery can improve the power performance, high-temperature cycle performance and high-temperature storage performance of the battery.

[0028] In some embodiments, based on the total mass of the electrolyte, the mass of the compound represented by Formula 1 accounts for 0.3%-4%. Thus, adding the electrolyte to a lithium-ion battery can improve the power performance, high-temperature cycle performance, and high-temperature storage performance of the battery.

[0029] In some embodiments, the electrolyte further includes a solvent, and the solvent includes a cyclic solvent.

[0030] In some embodiments, the cyclic solvent includes at least one of butylene carbonate, ethylene carbonate, fluoroethylene carbonate, propylene carbonate, or 1,4-butyrolactone.

[0031] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the cyclic solvent is 10%-30%.

[0032] The third aspect of the present application provides a battery, comprising the electrolyte described in the second aspect, so that the battery has excellent power performance, high temperature cycle performance and high temperature storage performance.

[0033] In some embodiments, the battery includes a positive electrode active material, the positive electrode active material includes LiCoO2, LiMn2O4, Li 1+y Mn 1-x M x O2、LiFe 1-x M x PO4 and Li2Mn 1-x O4, wherein M includes at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V and Ti, 0≤y≤0.2, 0≤x<1.

[0034] In some embodiments, the positive electrode active material includes LiCoO2 and Li1+y Mn 1-x M x At least one of O2, and M includes at least two of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V and Ti.

[0035] The fourth aspect of the present application provides an electric device, wherein the electric device comprises the battery according to the third aspect, so that the electric device has an excellent cycle life.

[0036] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0038] Figure 1 This is the theoretically calculated electrostatic potential diagram of 2,4-BS (the compound shown in Formula 1). DETAILED DESCRIPTION

[0039] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.

[0040] The technical solution of the present application was completed by the inventors based on the following findings: 2,4-BS (the compound shown in Formula 1), as a derivative of PS (1,3-propane sultone), is added to the battery. During the battery formation and cycle process, it can also form a SEI film rich in alkyl sulfonate lithium and inorganic sulfide on the surface of the negative electrode plate. Therefore, it is often used to replace PS to solve the problem of poor high temperature performance of lithium-ion batteries. However, adding a small amount of 2,4-BS cannot participate in the repair process of the SEI film in the later stage of the charge and discharge cycle, and cannot guarantee the stability of the lithium-ion battery in the later stage of the charge and discharge cycle; although increasing the amount of 2,4-BS added can form a large amount of SEI film rich in S elements to ensure the stability at the negative electrode-electrolyte interface, it was found during use that it will cause obvious gas production in lithium-ion batteries during high-temperature storage. The inventors have conducted in-depth research on this phenomenon and through theoretical calculations (electrostatic potential, such as Figure 1 As shown in Figure 2, it is found that the electron cloud of 2,4-BS is unevenly distributed, and its negative electron cloud has a higher charge. This means that the free radical containing sulfonate group formed after the ring opening of 2,4-BS is more inclined to donate electrons. This free radical will attack the cyclic solvent in the electrolyte, causing it to decompose and form ethylene, carbon dioxide, carbon monoxide and other gases, resulting in gas production in the battery.

[0041] In view of this, the first aspect of the present application proposes an electrolyte additive, wherein the electrolyte additive comprises a compound represented by Formula 1 and a protective agent. The protective agent comprises a chain compound with an unsaturation degree greater than or equal to 3, and the protective agent can undergo an addition reaction with a free radical containing a sulfonate group formed after the ring-opening reaction of the compound represented by Formula 1.

[0042] The electrolyte additive of the present application includes a compound shown in Formula 1 and a protective agent. The electrolyte additive is added to a lithium ion battery. During the formation and circulation process, the compound shown in Formula 1 can undergo a ring-opening reaction to produce a free radical containing a sulfonate group. The protective agent of the present application includes a chain compound with a degree of unsaturation greater than or equal to 3, which has a high activity and can preferentially react with the free radical containing a sulfonate group generated by the compound shown in Formula 1 before the cyclic solvent in the electrolyte, that is, the catalytic decomposition of the sulfonate group by the free radical containing the sulfonate group on the cyclic solvent is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high-temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to produce a free radical containing a sulfonate group, which reacts with the protective agent to form a dense SEI film rich in S elements on the negative electrode surface, which can improve the conductivity of the SEI film and improve the power performance of the battery. The SEI film has a high strength, which reduces the damage and recombination of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery. In addition, the protective agent used in the present application is a chain compound. Compared with the cyclic compound, the protective agent of the chain compound in the present application has higher activity and is more likely to undergo addition reaction with the free radical containing sulfonate group generated by the ring opening of the compound shown in Formula 1. Therefore, adding the electrolyte additive to the lithium-ion battery can improve the power performance, high temperature cycle performance and high temperature storage performance of the battery.

[0043] In the present application, the degree of unsaturation in the protective agent = the number of double bonds in the protective agent + the number of triple bonds in the protective agent × 2. And because the "protective agent" can react with the compound shown in Formula 1 to generate free radicals containing sulfonate groups in a ring-opening reaction before the cyclic solvent, that is, it protects the cyclic solvent, it is called a "protective agent".

[0044] In some embodiments of the present application, the protective agent includes a chain compound with an unsaturation of 3-8, for example, the unsaturation of the protective agent is 3, 4, 5, 6, 7, 8. As a result, the protective agent of the present application has a high activity, and can react with the free radical containing sulfonate group generated by the compound shown in Formula 1 in priority to the cyclic solvent in the electrolyte, that is, the catalytic decomposition of the free radical containing sulfonate group on the cyclic solvent is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to generate a free radical containing sulfonate group, which reacts with the protective agent of the composition to form a dense SEI film rich in S elements on the surface of the negative electrode, which can improve the conductivity of the SEI film and improve the power performance of the battery. In addition, the SEI film has a high strength, which reduces the damage and reorganization of the SEI film during the high temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high temperature cycle performance of the battery. In addition, the unsaturated protective agent can also reduce the problem of high battery impedance caused by too many unsaturated bonds participating in the formation of SEI film.

[0045] In some embodiments of the present application, the mass ratio of the compound shown in the above formula 1 to the protective agent is 0.7-11:1, for example 0.7:1; 0.9:1; 1:1, 3:1, 5:1, 7:1, 9:1, 11:1, etc., or can be a range of any of the above numerical values. Thus, the compound shown in formula 1 and the protective agent are compounded according to the above mass ratio, so that the protective agent can fully combine with the free radical containing sulfonate group generated by the ring opening of the compound shown in formula 1, reduce the catalytic decomposition of the cyclic solvent by the free radical containing sulfonate group, inhibit the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases, reduce the volume expansion of the battery, and enhance the high temperature storage performance of the battery. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to generate free radicals containing sulfonate groups, which react with the protective agent to form a more dense SEI film rich in S elements on the surface of the negative electrode, which can improve the conductivity of the SEI film and the power performance of the battery. In addition, the SEI film has high strength, which reduces the damage and reorganization of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery.

[0046] In some embodiments of the present application, the chain compound having an unsaturation degree greater than or equal to 3 includes at least one of a silane compound, a carbonate compound and a sulfonate compound.

[0047] In some specific embodiments of the present application, the above-mentioned silane compound includes a compound represented by Formula 2:

[0048]

[0049] Among them, R1, R2, R3, and R4 are independently hydrogen, fluorine, an alkyl group having 1 to 10 carbon atoms, a silane group having 1 to 10 carbon atoms, a siloxane group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an alkenylsiloxane group having 2 to 10 carbon atoms, or an alkynylsiloxane group having 2 to 10 carbon atoms.

[0050] Therefore, the silane compound with an unsaturation degree greater than or equal to 3 of the composition can react with the sulfonate group-containing free radical generated by the compound shown in Formula 1 before the cyclic solvent in the electrolyte, that is, the catalytic decomposition of the sulfonate group-containing free radical on the cyclic solvent is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high-temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to generate a sulfonate group-containing free radical, which reacts with the silane compound to form a dense SEI film rich in S elements and Si elements on the negative electrode surface, which can improve the conductivity of the SEI film and improve the power performance of the battery. In addition, the SEI film has a high strength, which reduces the damage and recombination of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery. In addition, the Si atoms on the SEI film can easily react with F - The combination can reduce the HF content in the electrolyte, inhibit HF from corroding the positive electrode and causing the transition metal ions to dissolve into the electrolyte to catalyze the decomposition of the cyclic solvent. The SEI film formed can enhance the stability of the positive electrode-electrolyte interface and inhibit gas production.

[0051] As an example, the above-mentioned alkyl groups with 1-10 carbon atoms include but are not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, etc.; the silyl groups with 1-10 carbon atoms include but are not limited to trimethylsilyl, etc.; the siloxane groups with 1-10 carbon atoms include but are not limited to dimethylsiloxane, etc.; the alkenyl groups with 2-10 carbon atoms include but are not limited to vinyl, propenyl, butadienyl, pentadienyl, etc.; the alkynyl groups with 2-10 carbon atoms include but are not limited to ethynyl, propynyl, butynyl, etc.; the alkenylsiloxane groups with 2-10 carbon atoms include but are not limited to trivinylsiloxane, etc.; the alkynylsiloxane groups with 2-10 carbon atoms include but are not limited to ethynyldimethylsiloxane, etc.

[0052] In some specific embodiments of the present application, in the compound represented by the above formula 2, R1, R2, R3, and R4 are independently methyl, vinyl, ethynyl, ethynyldimethylsiloxane or trivinylsiloxane.

[0053] As an example, the silane compound includes at least one of the following compounds:

[0054]

[0055] Specifically, the CAS of the compound represented by Formula 2-1 is 1112-55-6; the CAS of the compound represented by Formula 2-1 is 1675-60-1; the CAS of the compound represented by Formula 2-3 is 75144-60-4; the CAS of the compound represented by Formula 2-4 is 4180-02-3; the CAS of the compound represented by Formula 2-5 is 18244-95-6.

[0056] In some specific embodiments of the present application, the carbonate compound includes a compound represented by Formula 3:

[0057] R5-A-R6

[0058] Formula 3

[0059] Wherein, A is an alkenyl group having 2-6 carbon atoms or an alkynyl group having 2-6 carbon atoms, R5 and R6 are independently hydrogen, fluorine, an alkyl group having 1-10 carbon atoms, an alkenyl group having 2-10 carbon atoms, an alkynyl group having 2-10 carbon atoms, an alkyl carbonate group having 2-10 carbon atoms, an alkyl sulfonate group having 1-10 carbon atoms, or a fluoroalkyl group having 1-10 carbon atoms, and at least one of R5 and R6 is an alkyl carbonate group having 2-10 carbon atoms.

[0060] Thus, the carbonate compound with an unsaturation greater than or equal to 3 of the composition can react with the free radical containing sulfonate group generated by the compound shown in Formula 1 in priority to the cyclic solvent in the electrolyte, that is, the catalytic decomposition of the free radical containing sulfonate group on the cyclic solvent is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high-temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to generate a free radical containing sulfonate group, which reacts with the carbonate compound to form a dense SEI film rich in S elements on the negative electrode surface, which can improve the conductivity of the SEI film and improve the power performance of the battery. The SEI film has a high strength, which reduces the damage and reorganization of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery. In addition, the carbonate compound of the composition has good compatibility with the electrolyte solvent, thereby reducing the side reactions of the electrolyte and reducing the gas production of the battery.

[0061] As an example, the above-mentioned alkyl carbonate groups having 2-10 carbon atoms include but are not limited to methyl carbonate groups, ethyl carbonate groups, etc.; the alkyl sulfonate groups having 1-10 carbon atoms include but are not limited to methyl sulfonate groups, ethyl sulfonate groups, etc.; the fluoroalkyl groups having 1-10 carbon atoms include but are not limited to trifluoromethyl groups, difluoroethyl groups, etc.

[0062] In some specific embodiments of the present application, in the compound represented by the above formula 3, R5 and R6 are alkyl carbonate groups having 1 to 10 carbon atoms, preferably diethyl carbonate groups.

[0063] As an example, the carbonate compound includes at least one of the following compounds: Specifically, the CAS of formula 3-1 is 197244-14-7; the CAS of formula 3-2 is 219839-52-8.

[0064] In some embodiments of the present application, the sulfonate compound includes a compound represented by Formula 4:

[0065]

[0066] Here, R7 and R8 are independently a hydrogen atom, a fluorine atom, an alkyl group having 1 to 10 carbon atoms, a fluoroalkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms.

[0067] Thus, the sulfonate compound with an unsaturation greater than or equal to 3 of the composition can react with the sulfonate group-containing free radical generated by the compound shown in Formula 1 in priority to the cyclic solvent in the electrolyte, that is, the catalytic decomposition of the sulfonate group-containing free radical on the cyclic solvent is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high-temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to generate a sulfonate group-containing free radical, which reacts with the sulfonate compound to form a dense SEI film rich in lithium sulfonate and inorganic sulfide components on the negative electrode surface, which can improve the conductivity of the SEI film and improve the power performance of the battery. In addition, the SEI film has a high strength, which reduces the damage and reorganization of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery.

[0068] In some specific embodiments of the present application, R7 and R8 in the above formula 4 are independently methyl, trifluoromethyl, ethynyl, vinyl or fluorine atoms.

[0069] As an example, the sulfonate compound includes at least one of the following compounds:

[0070]

[0071] Specifically, the CAS of formula 4-1 is 16156-58-4; the CAS of formula 4-2 is 7459-72-5; and the CAS of formula 4-3 is 41029-46-3.

[0072] The second aspect of the present application provides an electrolyte, comprising the electrolyte additive described in the first aspect. Thus, adding the electrolyte to a lithium-ion battery can improve the high-temperature cycle performance and high-temperature storage performance of the battery.

[0073] In some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the compound shown in Formula 1 is 0.3%-4%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc., or it can be a range composed of any of the above numerical values. Therefore, on the one hand, the compound shown in Formula 1 with this content can meet the needs of the SEI film repair process in the later stage of the battery charge and discharge cycle, and improve the stability of the battery in the later stage of the cycle. On the other hand, due to the presence of the protective agent in the electrolyte additive, it can react with the sulfonate-containing free radicals generated by the cyclic solvent in the electrolyte in priority to the cyclic solvent in the electrolyte, that is, it reduces the catalytic decomposition of the sulfonate-containing free radicals on the cyclic solvent, inhibits the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases, reduces the volume expansion of the battery, and enhances the high temperature storage performance of the battery. On the other hand, the compound represented by Formula 1 at this content participates in the film formation process of the SEI film, making the SEI film rich in S elements, which can improve the conductivity of the SEI film and the power performance of the battery. In addition, the SEI film has high strength, which reduces the damage and reorganization of the SEI film during the high-temperature cycle process of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery.

[0074] In some embodiments of the present application, the electrolyte further includes a solvent, and the solvent includes a cyclic solvent. As an example, the cyclic solvent includes at least one of butylene carbonate, ethylene carbonate, fluoroethylene carbonate, propylene carbonate or 1,4-butyrolactone.

[0075] In some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the cyclic solvent is 10%-30%, such as 10%, 15%, 20%, 25%, 30%, etc., or can be a range composed of any of the above values. Thus, by adding this amount of cyclic solvent to the electrolyte, the thermal stability of the electrolyte can be improved and the side reactions of the electrolyte can be reduced.

[0076] In some embodiments of the present application, the electrolyte may further include other solvents, for example, at least one of diethyl carbonate, dimethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate.

[0077] In some embodiments of the present application, the electrolyte may further include an electrolyte salt, and the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0078] In some embodiments of the present application, the electrolyte may also include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0079] It should be noted that the negative electrode film-forming additives, positive electrode film-forming additives and additives that can improve certain battery properties are all types of additives commonly used in the field. Those skilled in the art can choose according to actual needs and will not be elaborated here. The characteristics and advantages described for the above-mentioned electrolyte additives are also applicable to the electrolyte and will not be elaborated here.

[0080] The third aspect of the present application provides a battery. According to an embodiment of the present application, the battery includes the electrolyte described in the second aspect.

[0081] Thus, during the battery formation and cycle process, the compound shown in Formula 1 in the electrolyte additive undergoes a ring-opening reaction to produce free radicals containing sulfonate groups. The protective agent in the electrolyte additive has a higher activity and can react with the free radicals containing sulfonate groups generated by the compound shown in Formula 1 in preference to the cyclic solvent in the electrolyte, i.e., the catalytic decomposition of the cyclic solvent by the free radicals containing sulfonate groups is reduced, and the decomposition of the cyclic solvent at high temperature to produce ethylene, carbon dioxide, carbon monoxide and other gases is inhibited, the volume expansion of the battery is reduced, and the high-temperature storage performance of the battery is enhanced. At the same time, the compound shown in Formula 1 undergoes a ring-opening reaction to produce free radicals containing sulfonate groups, which react with the chain compound with an unsaturation greater than or equal to 3 to form a dense SEI film rich in S elements on the negative electrode surface, which can improve the conductivity of the SEI film and improve the power performance of the battery, and the SEI film has a higher strength, which reduces the damage and reorganization of the SEI film during the high-temperature cycle of the battery, thereby reducing the consumption of active lithium and improving the high-temperature cycle performance of the battery. Thus, the battery of the present application has higher high-temperature storage performance and high-temperature cycle performance.

[0082] In some embodiments of the present application, the battery includes a positive electrode active material, and the positive electrode active material includes LiCoO2, LiMn2O4, Li 1+y Mn 1-x M x O2、LiFe 1-x M xPO4 and Li2Mn 1-x O4, wherein M includes at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V and Ti, 0≤y≤0.2, 0≤x<1.

[0083] As an example, Li 1+y Mn 1-x M x O2、LiFe 1-x M x PO4 and Li2Mn 1-x In O4, x can be 0, 0.1, 0.3, 0.5, 0.7, 0.9, etc., or can be any range of the above values; y can be 0, 0.1, 0.2, etc., or can be any range of the above values. 1+y Mn 1-x M x O2 may include but is not limited to LiMnO2, LiMn 0.5 Co 0.3 Ni 0.2 O2、Li 1.2 Mn 0.5 Co 0.3 Ni 0.2 O2, etc.; LiFe 1-x M x PO4 can include but is not limited to LiFePO4, LiFe 0.8 Mn 0.2 PO4, etc.; Li2Mn 1- x O4 may include but is not limited to Li2MnO4 and the like.

[0084] In some embodiments of the present application, the positive electrode active material includes LiCoO2 and Li 1+y Mn 1-x M x O2, M includes at least two of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V and Ti, such as LiNi 0.5 Co 0.3 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.65 Co 0.25 Mn 0.1 O2、LiNi 0.7 Co 0.2 Mn 0.1 O2、LiNi 0.7 Co 0.2 Al0.1 O2、LiNi 0.5 Co 0.3 Al 0.2 O2, etc. Specifically, when ternary active materials and lithium cobalt oxide are used as positive active materials for lithium-ion batteries, lithium-ion batteries often experience gas expansion and capacity decay, which is more obvious under high temperature conditions. These phenomena are usually caused by the intensification of side reactions of the electrolyte, and the intensification of problems such as the decomposition of lithium salts, the dissolution of transition metal ions, and the microcracks of the positive electrode material crystals under high temperature conditions will cause the side reactions of the electrolyte to become more serious, ultimately leading to serious gas production and capacity decay. The electrolyte can form a CEI film and SEI film with good thermal stability and density at the electrode-electrolyte interface by adding an electrolyte additive including a compound shown in Formula 1 and a protective agent, which can effectively inhibit the side reactions of the electrolyte on the electrode surface, and can effectively inhibit the erosion of the positive electrode active material by the byproducts of the decomposition of the electrolyte, thereby inhibiting the dissolution of transition metal ions and the formation of microcracks, and further inhibiting the occurrence of electrolyte side reactions. In summary, the electrolyte additive of the present application can enhance the stability of the ternary active material and the lithium cobalt oxide positive electrode, thereby inhibiting the gas production phenomenon and capacity decay problems.

[0085] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0086] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material mentioned above.

[0087] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0088] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0089] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0090] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0091] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0092] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0093] In some embodiments of the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0094] In some embodiments of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0095] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0096] In some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0097] In some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0098] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0099] In some embodiments of the present application, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0100] It should be noted that the above-described features and advantages of the electrolyte are also applicable to the battery and will not be described in detail here.

[0101] In a fourth aspect, the present application provides an electric device, the electric device comprising the battery described in the third aspect. Thus, the electric device has an excellent service life. For example, the electric device may include but is not limited to a mobile phone, a laptop computer, a pure electric vehicle, a hybrid electric vehicle, etc.

[0102] It should be noted that the features and advantages described above for the battery are also applicable to the electrical device and will not be described in detail here.

[0103] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0104] Example 1

[0105] 1. Preparation of positive electrode sheet

[0106] The positive electrode active material LiNi 0.8 Co0.1 Mn 0.1 O2, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) in a mass ratio of 96.8:2:1.2 to prepare a positive electrode slurry (the solid content in the positive electrode slurry is 68wt%). The positive electrode slurry is coated on the upper and lower surfaces of the aluminum foil, dried, and then cold pressed. The positive electrode sheets are then trimmed, cut, and stripped.

[0107] 2. Preparation of negative electrode sheet

[0108] Graphite, conductive carbon black, thickener carboxymethyl cellulose (CMC), and adhesive styrene-butadiene rubber (SBR) are mixed in deionized water at a mass ratio of 95:1.5:2:1.5 to form a negative electrode slurry (the solid content in the negative electrode slurry is 49wt%), the negative electrode slurry is coated on the upper and lower surfaces of copper foil and dried, and then cold pressed, trimmed, cut into pieces, and slit into strips to form negative electrode sheets.

[0109] 3. Preparation of electrolyte

[0110] In a glove box filled with argon, an electrolyte additive including a protective agent of Formula 2-1 and a compound represented by Formula 1 is added to an organic solvent (the organic solvent includes ethylene carbonate, ethyl methyl carbonate and diethyl carbonate. Based on the total mass of the electrolyte, the mass proportion of ethylene carbonate is 30%, the mass proportion of ethyl methyl carbonate is 43.75%; the mass proportion of diethyl carbonate is 13.75%), and after mixing evenly, LiPF6 is slowly added. After the lithium salt is completely dissolved, an electrolyte with a lithium salt concentration of 1 mol / L is obtained.

[0111] 4. Isolation film

[0112] A 16 μm polyethylene film was used as the separator.

[0113] 5. Lithium-ion battery preparation

[0114] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets to isolate the positive and negative electrodes, and the bare battery cell is wound, and the pole ears are welded. The bare battery cell is placed in an outer package, and the prepared electrolyte is injected into the dried battery cell. The lithium-ion battery cell is packaged, allowed to stand, formed, and shaped to complete the preparation of the lithium-ion battery.

[0115] The preparation methods of lithium-ion batteries of Examples 2-28 and Comparative Examples 1-17 are the same as those of Example 1, except that the additive composition and solvent composition in the electrolyte are different, as shown in Table 1; the preparation methods of lithium-ion batteries of Example 29 and Comparative Examples 15-17 are the same as those of Example 1, except that LiCoO2 is used as the positive electrode active material.

[0116] Table 1

[0117]

[0118]

[0119]

[0120]

[0121]

[0122] Note: In the above Table 1, "the composition is A+B, and the amount added in the electrolyte is a+b" can be understood as "the composition is a mixture of A and B, and the corresponding proportion of A is a%, and the proportion of B is b%".

[0123] The power performance, cycle performance and high temperature storage performance of the lithium ion batteries obtained in Examples 1-29 and Comparative Examples 1-17 were characterized. The characterization results are shown in Table 2.

[0124] Lithium-ion battery cycle performance and power performance test methods:

[0125] Charge at 45°C at a constant current of 1.0C to 4.4V, then charge at a constant voltage to a cutoff current of 0.05C, and then discharge the battery at a constant current of 1.0C. The discharge capacity is recorded as C0. Repeat the charge and discharge until the capacity decays to 80% of C0 and record the number of cycles.

[0126] Take the above-mentioned battery that has been cycled at high temperature to 80% C0, charge it to 4.4V with 1C, then charge it to 0.05C at constant voltage, let it stand for 30min, then discharge it at 1C for 0.5h, let it stand for 30min, record the voltage V1 after standing, then discharge it at 2C for 10s, with a sampling interval of 0.1S, and record the voltage V2 at the end of discharge. Battery DCR (DC internal resistance) = (V1-V2) / I, I = 2C.

[0127] Lithium-ion battery high temperature storage performance test method:

[0128] At 25°C, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, and then discharge the battery at 0.5C constant current, and the discharge capacity is recorded as C1. Remove the battery and use a thickness tester to test its initial thickness, which is T1. At 25°C, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, and then transfer the battery to 60°C for 15 days. Use a thickness tester to test its thickness after 15 days, which is T2. Then discharge the battery at 1.0C constant current, and the discharge capacity is recorded as C2. After 15 days of storage at 60°C, the capacity retention rate = C2 / C1*100%, and the battery expansion rate = 100%*(T2-T1) / T1.

[0129] Table 2

[0130]

[0131]

[0132]

[0133] Conclusion: It can be seen from the data in Table 2 that compared with Comparative Examples 1-2, the DCR and expansion rate after cycling of the lithium battery of Example 1-29 are significantly lower than those of Comparative Examples 1-2, and the 60°C storage capacity retention rate and cycle performance of the lithium battery of Example 1-29 indicate that the present application can improve the power performance, high temperature storage and cycle performance of the lithium battery by adding an electrolyte additive comprising a compound represented by Formula 1 and a chain compound having a degree of unsaturation greater than or equal to 3 into the electrolyte.

[0134] Compared with Comparative Example 3 in Example 1, compared with Comparative Example 4 in Example 2, compared with Comparative Example 3 in Example 5, compared with Comparative Example 4 in Example 6, compared with Comparative Example 5 in Example 7, compared with Comparative Example 6 in Example 8, compared with Comparative Example 7 in Example 9, compared with Comparative Example 10 in Example 9, compared with Comparative Example 11 in Example 10, and compared with Comparative Example 12 in Example 10, the lithium ion batteries of Examples 1-10 have higher DCR, 60°C storage capacity retention rate, cycle performance and expansion rate after cycling. This is because the compound described in Formula 1 is added to the electrolyte additives of Examples 1-10, which will cause the electrolyte to produce gas, thereby increasing the expansion rate of the battery. However, the SEI membrane formed therefrom has higher ionic conductivity and density, thereby reducing the DCR of the battery and improving the 60°C storage capacity retention rate and cycle performance. Comparing Examples 1-10 and Comparative Example 13, the DCR of the lithium battery in Example 5 is higher. This is because the unsaturation degree of the protective agent used in Example 5 is 3, and the degree of polymerization thereof with the compound of Formula 1 is low, so less S element is formed in the SEI film, which leads to an increase in its DCR; however, the 60°C storage capacity retention rate and cycle performance of the lithium batteries in Examples 1-10 are higher and the expansion rate is lower. This is because the protective agent used in Examples 1-10 is a chain compound, which is easier to form a film, and the formed SEI film has a higher thermal stability, so the DCR and expansion rate of the lithium ion battery after cycling can be reduced, and the 60°C storage capacity retention rate and cycle performance of the lithium battery can be improved.

[0135] Comparing Examples 1-10 and Comparative Example 14, the 60°C storage capacity retention rate and cycle performance of the lithium ion battery of Example 1-10 are higher, and the expansion rate and DCR are lower. This is because the protective agent used in Example 1-10 is a chain compound, which is easier to form a film, and the formed SEI film has a higher thermal stability, so the DCR and expansion rate of the lithium ion battery after cycling can be reduced, and the 60°C storage capacity retention rate and cycle performance of the lithium battery can be improved. Comparing Example 29 and Comparative Examples 15-17, Example 29 has a higher 60°C storage capacity retention rate and cycle performance of the lithium ion battery and a lower expansion rate and DCR than Comparative Examples 15-16; Example 29 has a lower expansion rate than Comparative Example 17, because the compound described in Formula 1 is added to the electrolyte additive of Example 29, which causes the electrolyte to produce gas, thereby increasing the expansion rate of the lithium ion battery, but the SEI film formed by it has a higher ionic conductivity and density, thereby reducing the DCR of the battery and improving the 60°C storage capacity retention rate and cycle performance.

[0136] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0137] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. An electrolyte additive, characterized in that: It comprises a compound represented by formula 1 and a protective agent, The protective agent comprises a chain compound with an unsaturation degree greater than or equal to 3, and the protective agent can undergo an addition reaction with a free radical containing a sulfonate group formed after the ring-opening reaction of the compound represented by Formula 1.

2. The electrolyte additive according to claim 1, characterized in that: The protective agent includes a chain compound with an unsaturation degree of 3-8.

3. The electrolyte additive according to claim 1 or 2, characterized in that: The mass ratio of the compound represented by formula 1 to the protective agent is 0.7-11:

1.

4. The electrolyte additive according to claim 1 or 2, characterized in that: The chain compound with an unsaturation degree greater than or equal to 3 includes at least one of a silane compound, a carbonate compound and a sulfonate compound.

5. The electrolyte additive according to claim 4, characterized in that: The silane compound includes a compound shown in Formula 2: Among them, R1, R2, R3, and R4 are independently hydrogen, fluorine, an alkyl group having 1 to 10 carbon atoms, a silane group having 1 to 10 carbon atoms, a siloxane group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an alkenylsiloxane group having 2 to 10 carbon atoms, or an alkynylsiloxane group having 2 to 10 carbon atoms.

6. The electrolyte additive according to claim 5, characterized in that: The R1, R2, R3, and R4 are independently methyl, vinyl, ethynyl, ethynyldimethylsiloxane or trivinylsiloxane.

7. The electrolyte additive according to claim 5 or 6, characterized in that: The silane compound includes at least one of the following compounds:

8. The electrolyte additive according to claim 5, characterized in that: The carbonate compound includes a compound shown in Formula 3: Wherein, A is an alkenyl group having 2-6 carbon atoms or an alkynyl group having 2-6 carbon atoms, R5 and R6 are independently hydrogen, fluorine, an alkyl group having 1-10 carbon atoms, an alkenyl group having 2-10 carbon atoms, an alkynyl group having 2-10 carbon atoms, an alkyl carbonate group having 2-10 carbon atoms, an alkyl sulfonate group having 1-10 carbon atoms, or a fluoroalkyl group having 1-10 carbon atoms, and at least one of R5 and R6 is an alkyl carbonate group having 2-10 carbon atoms.

9. The electrolyte additive according to claim 8, characterized in that: R5 and R6 are alkyl carbonate groups having 1 to 10 carbon atoms, preferably diethyl carbonate groups.

10. The electrolyte additive according to claim 8 or 9, characterized in that: The carbonate compound includes at least one of the following compounds:

11. The electrolyte additive according to claim 5, characterized in that: The sulfonate compound includes a compound shown in Formula 4: Here, R7 and R8 are independently a hydrogen atom, a fluorine atom, an alkyl group having 1 to 10 carbon atoms, a fluoroalkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms.

12. The electrolyte additive according to claim 11, characterized in that: R7 and R8 are each independently a methyl group, a trifluoromethyl group, an ethynyl group, a vinyl group or a fluorine atom.

13. The electrolyte additive according to claim 11 or 12, characterized in that: The sulfonate compound includes at least one of the following compounds:

14. An electrolyte, characterized in that: The electrolyte additive comprises the electrolyte additive described in any one of claims 1 to 13.

15. The electrolyte according to claim 14, characterized in that Based on the total mass of the electrolyte, the mass proportion of the compound represented by Formula 1 is 0.3%-4%.

16. The electrolyte according to claim 15, characterized in that The electrolyte further includes a solvent, wherein the solvent includes a cyclic solvent; Optionally, the cyclic solvent includes at least one of butylene carbonate, ethylene carbonate, fluoroethylene carbonate, propylene carbonate or 1,4-butyrolactone.

17. The electrolyte according to claim 16, characterized in that Based on the total mass of the electrolyte, the mass proportion of the cyclic solvent is 10%-30%.

18. A battery, characterized in that: The invention comprises the electrolyte described in any one of claims 14 to 17.

19. The battery according to claim 18, characterized in that The battery includes a positive electrode active material, wherein the positive electrode active material includes LiCoO2, LiMn2O4, Li 1+y Mn 1-x M x O2、LiFe 1-x M x PO4 and Li2Mn 1-x At least one of O4, Wherein, M includes at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V and Ti, 0≤y≤0.2, 0≤x<1; Optionally, the positive electrode active material includes LiCoO2 and Li 1+y Mn 1-x M x At least one of O2, and M includes at least two of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V and Ti.

20. An electrical device, characterized in that: Comprising the battery according to claim 18 or 19.

Citation Information

Cited By

  • Electrolyte additive, electrolyte, battery and electric device

    EP4779743A1

  • Electrolyte additive, electrolyte, battery and electric device

    WO2025082255A1